Evidence for two-band magnetotransport in half-metallic chromium dioxide - COEY, JOHN MICHAEL DAVID (American Physical Society, 2000)
Magnetotransport measurements were made on patterned, (110) oriented CrO2 thin films grown by the high-pressure, thermal decomposition of CrO3 onto rutile substrates. The low-temperature Hall effect exhibits a sign reversal from positive to negative as the magnetic field is increased above 1 T, which may be interpreted within a simple two-band model as indicating the presence of highly mobile (?h=0.25 m2/V s) holes as well as a much larger number of less mobile electrons (n=0.4 electrons/Cr). Between 50 and 100 K, the field at which the sign reversal occurs rapidly increases and a contribution from the anomalous Hall effect becomes significant, while the large, positive transverse magnetoresistance (MR) observed at low temperatures changes over to a predominantly negative MR. These changes correlate with a thermally activated dependence in the resistivity of the form T2e-?/T with ?~80 K, reflecting the lack of temperature dependence in the resistivity at low temperatures and a T2 behavior above 100 K. The high mobilities at low temperature which result in the observed positive MR reflect the suppression of spin-flip scattering expected for a half-metallic system. However, the changes in magnetotransport above the temperature ? must be due to the onset of spin-flip scattering, even though kB? is much less than the expected energy gap in the minority spin density of states. The significance of ? is discussed in terms of recent models for another half-metallic system, the perovskite manganites, and the possible formation of ``shadow bands.''
PUBLISHED
Keywords: Physics